18 reform university in Argentina analyzed from the drive model - Mazzola, Carlos (Universidade Estadual de Campinas, 2016)
The university reform originated in the province of Cordoba in 1918 forged the political and organizational matrix of the Argentina University. The model spans several countries in Latin America and persists as a reference reality and Argentine university actors. The proposed revision is not only socio-historical methodology, while it is done from a conceptual framework that unit as part conceptual model. This model allows resignificar issues and conflicts with the reformists rallied 18.